MIGRASI LEGAL DAN ILEGAL KE MALAYSIA BARAT: KASUS MIGRASI INTERNASIONAL DI PULAU LOMBOK, NUSA TENGGARA BARAT - Bambang Wicaksono Triantoro (Populasi, 1999)
The problem of Indonesian illegal migrant workers to foreign countries will always be a crucial issue. The international migrant workers issue raised when many Indonesian migrant workers to foreign countries were treated badly when seen from a humanity and law aspect. The data of this research made use of the research data conducted by the International Migration Team, Population Studies Center, Gadjah Mada University comprising of 355 return migrants from Lombok Island, West Nusa Tenggara in 1998. The return migrants acted as respondents were randomly selected. The method used in this research were quantitative and qualitative with secondary data analysis. Results of the research indicated that individual, institutional (structural) and environmental context influences the program effectiveness. The institutional context such as bureaucracy and the environmental context were the existence of informal institution and accessibility of also gives contribution towards consideration in determining the choice of the migration procedure, especially in determining the legal migration procedure